2017
DOI: 10.1017/s0020818317000236
|View full text |Cite
|
Sign up to set email alerts
|

(When) Do Antipoverty Programs Reduce Violence? India's Rural Employment Guarantee and Maoist Conflict

Abstract: Theory and extensive evidence connect poverty and underdevelopment to civil conflict yet evidence on the impact of development programs on violence is surprisingly mixed. To break this impasse, we exploit a within-country policy experiment to examine the conditions under which antipoverty programs reduce violence. The roll-out of India's National Rural Employment Guarantee Scheme caused a large long-run reduction in Maoist conflict violence, as measured with an original data set based on local-language press s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Vanden Eynde (2016) and find evidence in support of an opportunity cost channel driving Maoist conflict. Dasgupta et al (2017), which is closely related to this paper, use a difference-in-differences approach to compare districts that received NREGA early with those that received it later; they find that the introduction is correlated with a reduction in conflict. This approach is not without problems because the sequence of NREGA's roll-out was far from random.…”
Section: Introductionmentioning
confidence: 83%
“…Vanden Eynde (2016) and find evidence in support of an opportunity cost channel driving Maoist conflict. Dasgupta et al (2017), which is closely related to this paper, use a difference-in-differences approach to compare districts that received NREGA early with those that received it later; they find that the introduction is correlated with a reduction in conflict. This approach is not without problems because the sequence of NREGA's roll-out was far from random.…”
Section: Introductionmentioning
confidence: 83%
“…The district-level controls (μ) include district domestic product per capita (DDP) as a control for demand conditions and number of bank branches per 1,000 persons as a proxy for financial infrastructure, η represents year effects and finally, ε is the random error term. Akin to Dasgupta et al (2017), all regressions control for the score of the district on the backwardness index (BI), interacted with year dummy variables, so as to minimize possible concerns regarding non-parallel time trends across different phases, emanating from the assignment of less developed districts as measured on the backwardness index to earlier phases of the programme.…”
Section: Methodsmentioning
confidence: 99%
“…To provide some examples, Barooah (2008) employs an ordinary least squares (OLS) framework and finds that Maoist conflict violence across districts increases with poverty and declines with literacy. Dasgupta, Gawande and Kapur (2017) along with Fetzer (2014) find that the effect of Maoist violence is mitigated by the roll-out | 21 GHOSH of a large public works programme (MGNREGS) in Maoist-affected states. In contrast, Khanna and Zimmermann (2017) argue that LWE violence increases after the introduction of MGNREGS because of the increased polarization of the civilian population between government and Maoist supporters.…”
mentioning
confidence: 99%
“…In their analysis, the authors found that the programme reduced conflict related incidents and insurgent influence in treated villages by weakening for the deleterious effect it had on insurgent recruitment. Dasgupta, Gawande, and Kapur (2014) estimated the effects of the National Rural Employment Guarantee Scheme (NREGS) on the Maoist conflict in India. The authors found that the programme reduced violent incidents and deaths, providing evidence of the effects of this policy on the mitigation of violent civil conflict.…”
Section: Introductionmentioning
confidence: 99%